ANTI-OXIDANT AND ANTI-DIABETIC ACTIVITIES OF ETHANOLIC EXTRACT OF Primula denticulata FLOWERS - Hemlata Bhatt; Sarla Saklani; Kumud Upadhayay (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
The present investigation was carried out to focus on the anti-oxidant and anti-diabetic effect of ethanolic extract of flowers of Primula denticulata by DPPH, ferrous chelating, reducing power assay and streptozotocin induced diabetes respectively. Dose selection was made on the basis of acute oral toxicity study (100mg/kg, 200mg/kg, 400mg/kg bodyweight) as per OECD guidelines 423. The blood glucose levels were measured by using blood glucose measuring strips based on glucose-oxidase method. The extract showed significant anti-oxidant and anti-diabetic activity when compared with standard drug.Keywords: Primula denticulata, anti-oxidant and anti-diabetic activity.